Stranger beside me: Ted Bundy, the classic case of serial murder - Rule, Ann frey50 (New York. W. W. Norton & Comp., 1980)
Ted Bundy was handsome, charming, brilliant in law school, and on the verge of a dazzling career. On January 24, 1989, he was executed for the murders of three young women, having confessed to taking the lives of at least thirty-five more. This is the story of one of the most fascinating killers in American history - of his magnetic power, his bleak compulsion, his double life, his tring of vulnerable victims.
Keywords: Criminals -- United States -- Biography; Serial murder - United States - Biography